The Influence of Teachers’ Personality Traits on Students’ Motivation to Learn Religion at SMPN 7 IT Dompu in the 2024 Academic Year - Muhammad Amin; Firmansyah Firmansyah (JURNAL PENDIDIKAN IPS, 2025)
Teachers play a central role in education, holding a crucial position in the overall learning process at school. A teacher's personality is an essential requirement that must be possessed by an educator as a professional, as it significantly influences the success of a teacher in carrying out their duties. These duties are not limited to delivering knowledge but also include instilling noble values in students. Based on this line of thought, a teacher's personality becomes an attraction for students in engaging with the learning process in the classroom, thereby fostering their learning motivation. This study aims to determine the influence of teachers’ personality traits on students’ motivation to learn religion at SMPN 7 IT in the 2024 academic year. The research uses a quantitative approach with a correlational research type. The data analysis technique employed in this study is the product-moment correlation analysis. The results of this study are as follows: (1) It is known that the quality of students’ religious learning motivation, influenced by the teachers’ personality traits at SMPN 7 IT Dompu, is quite good and falls into the high category. (2) It is evident that there is a positive and significant influence between teachers’ personality traits and students’ motivation to learn religion at SMPN 7 IT in the 2024 academic year.